2009
DOI: 10.1084/jem.20091240
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene E4–induced pulmonary inflammation is mediated by the P2Y12 receptor

Abstract: Of the potent lipid inflammatory mediators comprising the cysteinyl leukotrienes (LTs; LTC4, LTD4, and LTE4), only LTE4 is stable and abundant in vivo. Although LTE4 shows negligible activity at the type 1 and 2 receptors for cys-LTs (CysLT1R and CysLT2R), it is a powerful inducer of mucosal eosinophilia and airway hyperresponsiveness in humans with asthma. We show that the adenosine diphosphate (ADP)–reactive purinergic (P2Y12) receptor is required for LTE4-mediated pulmonary inflammation. P2Y12 receptor expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
240
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 224 publications
(252 citation statements)
references
References 58 publications
9
240
2
1
Order By: Relevance
“…Oral administration of zileuton to subjects with AERD blocked the release of tryptase into the nasal lavage fluid following intranasal Lys-ASA challenge (50). MCs express all of the known CysLTRs (14)(15)(16)51), and blockade of CysLT 1 R with montelukast mirrored the effect of zileuton on the release of MC activation products in our study. Thus, AERD involves a prominent autocrine and/or paracrine signaling loop in which cysLTs promote MC activation.…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducesupporting
confidence: 65%
“…Oral administration of zileuton to subjects with AERD blocked the release of tryptase into the nasal lavage fluid following intranasal Lys-ASA challenge (50). MCs express all of the known CysLTRs (14)(15)(16)51), and blockade of CysLT 1 R with montelukast mirrored the effect of zileuton on the release of MC activation products in our study. Thus, AERD involves a prominent autocrine and/or paracrine signaling loop in which cysLTs promote MC activation.…”
Section: Deletion Of Hematopoietic Ep 2 Receptors Partially Reproducesupporting
confidence: 65%
“…They are necessary for lung leukocyte recruitment in a murine model of allergic inflammation, and plateletleukocyte aggregates are formed in circulating blood of patients with asthma after allergen exposure [141]. It has been reported that the P2Y 12 receptor is required for proinflammatory actions of the stable abundant mediator LTE4 in allergic asthma and has been suggested to be a novel potential therapeutic target for asthma [142]. The specific contribution of the platelet P2 receptors in this disease warrants further studies as the P2Y 1 receptor has also been proposed to have a role in airways inflammation [143].…”
Section: The P2y 1 Receptor As a Target For New Antiplatelet Compoundsmentioning
confidence: 99%
“…The greater specificity of the mannitol test for detecting changes in airway hyper-responsiveness in asthma patients is likely explained by the fact that it mimics the normal pathophysiology of bronchial asthma, causing the release of various mediators of bronchoconstriction (76). Although the results of this study cannot clarify whether the effect of prasugrel was mediated by its interaction with P2Y 12 on platelets or other cells, the former hypothesis is supported by the results of experimental studies that demonstrated the important role of platelet P2Y 12 in the recruitment of inflammatory cells in lungs of sensitized mice challenged with cysteinyl-LT (70,71). Moreover, due to the very short half-life of the active metabolite of prasugrel, inhibition of P2Y 12 on nucleated cells, such as leukocytes, would likely be very short lived and probably insufficient to exert any clinically relevant effect (77).…”
Section: Allergic Bronchial Asthmamentioning
confidence: 59%
“…However, more recently GPR99 was identified as the elusive receptor for LTE 4 (67). Moreover, studies that demonstrated the important role played by platelet P2Y 12 in LTE 4 -or LTC 4 -induced enhanced recruitment of inflammatory cells in the lungs of sensitized mice failed to show that the CysLT interact directly with the platelet P2Y 12 , which might therefore play an indirect, albeit important role in the process (63,70,71).…”
Section: Allergic Bronchial Asthmamentioning
confidence: 99%